THU0325 THE HMGB1/AGE-RAGE AXIS IN SYSTEMIC SCLEROSIS PATIENTS: A POTENTIAL ROLE IN ITS VASCULOPATHY?. (June 2019) - Atzeni, Isabella; Abdulle, Amaal Eman; Roon, Anniek van; Diercks, Gilles; Goor, Harry van; Smit, Andries; Westra, Johanna; Mulder, Douwe J
Abstract : Background: Systemic sclerosis (SSc) is a progressive fibro-inflammatory autoimmune disease of which the pathogenetic pathways are incompletely understood. Advanced glycation endproducts (AGEs) are oxidative stress derived compounds with potential proinflammatory effects. Their exact role in fibrosis remains unknown. The receptor for AGEs is RAGE, which is also the receptor for high mobility group box 1 (HMGB1), a nuclear protein, which is proinflammatory when released from activated or apoptotic cells. We hypothesize that AGEs and HMGB1 may promote inflammation and profibrotic processes, presumably mediated by RAGE. Objectives: To study the role of the HMGB1/AGE-RAGE axis in the pathogenesis of SSc. Methods: Distribution of N Ɛ -(carboxymethyl)lysine (CML) and N δ -(5-hydro-5-methyl-4-imidazolon-2-yl)-ornithine (MG-H1) was assessed by immunohistochemistry in skin biopsies of 12 SSc patients [median age 56 years (IQR 52-61); 6 of affected, 6 of unaffected skin]. The intensity was assessed semi-quantitatively on endothelium and fibroblasts. In vitro experiments were performed on healthy human dermal fibroblasts, which were stimulated by HMGB1, AGE-BSA or TGF-β1 as control. Inflammatory and profibrotic markers were measured by ELISA and rt-PCR. Differentiation to myofibroblasts was assessed by staining of α-smooth muscle actin (α-SMA). In an additional clinical study, we included 20 SSc patients [51 years (44-58)] and 20 age- and sex-matched healthy controls [(HC) 52 years (45-62)]. Sera were obtained to determine CRP, ESR, HMGB1 and soluble RAGE (sRAGE) levels. AGE accumulation in skin was assessed as skin autofluorescence (SAF) by the AGE Reader. Results: MG-H1 staining was more intense on all skin structures in SSc patients, compared to HC, while CML staining showed no differences. MG-H1 was more pronouncedly detected on endothelium and fibroblasts in affected compared to unaffected skin. In vitro stimulation of fibroblasts with AGE-BSA resulted in increased expression of IL-6, collagen-1α and connective tissue growth factor. Finally, HMGB1 and AGE-BSA induced myofibroblast differentiation and formation of SMA fibers (Fig. 1, 2 ). In regards to the clinical study CRP (SSc: median 1.8 mg/l (IQR 0.8-3.5), HC: 0.7 (0.4-1.8), p=0.04), ESR (SSc: 8.5 mm/h (5.3-15.5), HC: 5.0 (3.0-7.0), p=0.02), HMGB1 (SSc: 3.4 ng/ml (1.6-6.1), HC: 1.6 (0.8-2.8), p=0.03), sRAGE (SSc: 956.3 pg/ml (717.9-1670.0), HC: 684.9 (517.0-890.5), p=0.02) and SAF (SSc: 2.2 AU (1.8-2.5), HC: 1.8 (1.4-2.1), p=0.02) were significantly increased in SSc patients, compared to HC. Conclusion: This is the first translational study that might indicate a prominent role of the HMGB1/AGE-RAGE axis in systemic sclerosis by promoting inflammation and fibrosis. Further studies investigating this pathway are ongoing. Acknowledgement: Actelion, for co-funding the clinical study. Disclosure of Interests: Isabella Atzeni: None declared, Amaal Eman Abdulle : None declared, Anniek van Roon: None declared, Gilles Diercks: None declared, Harry van Goor: None declared, Andries Smit Shareholder of: Has been co-founder, and is still shareholder of Diagnoptics Technologies, the company which developed the AGE reader., Johanna Westra: None declared, Douwe J Mulder Grant/research support from: My University has received research grants for my research from: Boehringer Ingelheim and Actelion, Speakers bureau: My University has received speakers fee from: Sanofi